Restaurant outlet density and the healthfulness of food purchases: evidence from FoodAPS - Volpe, Richard; Cai, Xiaowei; Tseng, Marilyn; Sinclair, Wilson (Frontiers in Nutrition, 2024)
We use the USDA's National Household Food Acquisition and Purchase Survey (FoodAPS) data and NPD ReCount data to investigate the associations between food outlet density and local diet quality, as measured by the Healthy Eating Index (HEI) of food purchases. Controlling for household demographics and the food-away-from-home environment, we find that neither restaurant counts nor openings share many statistically or economically significant associations with average dietary quality. We discuss important implications for food policy.